The Sage encyclopedia of children and childhood studies - Abebe, Tatek (Sage Publications. Inc., 2020)
This four-volume encyclopedia covers a wide range of themes and topics, including: Social constructions of childhood, Children's rights, Politics/representations/geographies, Child-specific research methods, Histories of childhood/Transnational childhoods, Sociology/anthropology of childhood theories and Theorists key concepts. This interdisciplinary encyclopedia will be of interest to students and researchers in: Childhood studies, Sociology/Anthropology, Psychology/Education, Social Welfare, Cultural studies/Gender studies/Disabilty studies
Enthält alle 4 Bände der Druckausgabe
Volume 1; List of Entries; Reader’s Guide; About the Editor; Contributors; Introduction; A; B; C; Volume 2; List of Entries; C (Cont.); D; E; F; G; Volume 3; List of Entries; H; I; J; K; L; M; N; O; P; Q; Volume 4; List of Entries; R; S; T; U; V; W; Y; Z; Index;
Keywords: Children / Encyclopedias; Child psychology / Encyclopedias; Pediatrics / Encyclopedias; Kindheitsforschung; Enzyklopädie